Reflections on the Relationship between Climate Change and Mobilities: Perspectives on Governance, Securitization, and Justice - Pérez Martínez, Lucía; Redín , Gabriel; Forero, Jorge Enrique (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2024)
In recent years, the issue of climate mobilities has been the subject of considerable discussion, not only in international climate governance forums, but also in academia and in the broader field of international cooperation. In this regard, this article aims to provide a narrative review of the existing literature on the subject, from which to identify some challenges for the future research agenda, especially that related to the governance of human mobility that, in our view, runs the risk of succumbing to securitarianism. Instead, we advocate for a political rather reflection on this phenomenon and for emphasizing migrant and climate justice as axes for future action.